Post-Traumatic Stress Disorder (PTSD) Among Healthcare Workers of Tertiary Care Hospitals of Rawalpindi; Amid the COVID-19 Pandemic - Mohsin, Shamaila; Zahoor, Mamoona; Mashhadi, Syed Fawad; Khan, Muhammad Arham; Khalid, Taimur; Amanullah, Mubaraka; Khan, Shumaila; Abbasi, Azwa; Khan, Saifullah (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the prevalence of PTSD symptoms and its severity among HCWs, amid the COVID pandemic in a tertiary care setting. Study Design: Cross sectional analytic study. Place and Duration of Study: Pakistan Emirates Military Hospital, Rawalpindi Pakistan, from May to Aug 22. Methodology: The study was conducted on 173 healthcare workers of a tertiary care hospital. The sample size was calculated using the Rao-soft calculator. Validated questionnaires such as the Impact of Event Scale-Revised (IES-R) and PTSD Checklist Civilian Version (PCL-C) were used to collect the data. Data was entered and analyzed by using Statistical Package for Social Sciences (SPSS) version 26. Results: Out of 173 participants, majority of participants 90(52%) were male and single 103(63%). Mean age of the participating HCWs was 27(SD= 2.3). HCWs performing duties the in COVID-19 ward for one year were 66(38.2%) and majority were from Emergency medicine 61(35.3). Almost 150(86.71%) of HCWs did not experiencing any PTSD symptoms and those exhibiting a higher severity of symptoms were only 5(2.9%). There was no statistically significant difference in total and sub scales mean scores of IES-R among males and females (p= 0.28). Conclusions: Our study concluded that prevalence of symptoms of PTSD was significantly low in Health Care Workers despite of the fact, majority of doctor participants were working in COVID-19 ward for one year. The symptoms were evident among healthcare professionals, however there was modest severity.